Assessment of the Geomagnetically Induced Current (GIC) at Low Latitude Region based on MAGDAS Data. (January 2019) - Mohd Anuar, N; Mohd. Kasran, F.A.; Abbas, M; Jusoh, M.H; Enche Ab Rahim, S.A; Abdul Hadi, N.; Yoshikawa, A.; Mohd. Radzi, Z
Abstract: The geomagnetically induced current (GICs) impact is no longer concentrated at high latitude region strictly. The objective of this study was to extend the GICs observation conducted at equatorial region using geomagnetic data extracted from magnetometer installed at Langkawi National Observatory (LNO), Malaysia for the long-term analysis involving the solar cycle 24. The observation is now continued with the GICs comparison between LKW stations with five low latitude station which is BCL, PTN, MND, DAW, and TWV obtained from the magnetic data acquisition system (MAGDAS). The assessment of the GICs behavior revealed the possibility of LKW station experiences GICs is high, based on the time derivative of the horizontal component (dH/dt) value. Extend from that, the GICs estimation was successful done by applying the plane wave method as a model to calculate the North-South and the East-West component, Ex and Ey respectively. The equation of the GICs was provided by excluding the topology constant parameters, which is a and b constant and the value of the underground conductivity for low latitude station. Subsequently, the comparison was limited in years of 2008 – 2014 due to insufficient geomagnetic data. Indeed, the GICs calculation is able to derive the GICs estimation and showed a good agreement with the corresponding value of the time derivative of the horizontal component. However, the accurate current value (A) is able to gain by conducting a direct measurement of the high voltage power transmission system.